Comparative Adult Mortality and Relative Attractiveness of Spotted-Wing Drosophila (Diptera: Drosophilidae) to Novel Attract-and-Kill (ACTTRA SWD) Formulations Mixed With Different Insecticides - Babu, Arun; Rodriguez-Saona, Cesar; Sial, Ashfaq A. (Frontiers in Ecology and Evolution, 2022)
Since its first appearance in California in 2008 and subsequent spread across the continental United States, the spotted-wing drosophila, Drosophila suzukii Matsumura, has become an economically damaging pest of multiple stone and soft-skinned fruits in the United States. The adjuvant ACTTRA SWD, when mixed with a suitable insecticide, constitutes an innovative attract-and-kill tactic that can be applied as a sprayable bait to manage D. suzukii. As an adjuvant, growers can mix ACTTRA SWD with any insecticide recommended for D. suzukii management in a specific crop; however, to achieve this, the efficacy of this adjuvant incorporated with various insecticides needs testing. This research aims to test the suitability of nine insecticides added to two ACTTRA SWD formulations (named OR1 and TD) to maintain the formulation's attractiveness to D. suzukii adults and in resulting mortality. We conducted a series of two-choice bioassays to test the relative attraction of D. suzukii to ACTTRA SWD formulations prepared with and without a specific insecticide. Additionally, we tested the efficacy of ACTTRA SWD formulations mixed with insecticides in managing D. suzukii by using no-choice efficacy bioassays. Adding Mustang Maxx (zeta-cypermethrin) to ACTTRA SWD OR1 significantly improved D. suzukii adult attraction to the formulation, while Azera (azadirachtin + pyrethrins) significantly reduced attraction to both ACTTRA SWD formulations. Among the insecticides tested, we identified Danitol (fenpropathrin), Exirel (cyantraniliprole), Malathion (malathion), Mustang Maxx, and Entrust (spinosad) as suitable insecticide additives for both ACTTRA SWD formulations. The results from this study will assist growers in selecting proper insecticide components when preparing attract-and-kill formulations of the new adjuvant ACTTRA SWD.